2019
DOI: 10.35590/jeb.v5i2.748
|View full text |Cite
|
Sign up to set email alerts
|

Pemetaan Potensi dan Minat Mahasiswa UPN “Veteranˮ Jakarta untuk Berwirausaha

Abstract: AbstrakPenelitian ini bertujuan untuk melakukan pemetaan tentang minat berwirausaha mahasiswa UPN ˮVeteranˮ Jakarta serta menguji tentang pengaruh antara Intention Credibility yaitu perceived desirability, Perceived feasibility, dan propensity to Act terhadap perilaku kewirausahaan (Entrepreneurial Behaviour) yang di indikasikan dengan atitude toward the behavior, subjective norm, dan perceived behavior control serta pengaruhnya terhadap enrerpreneurial intention (minat berwirausaha). Populasi dari penelitian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…People cannot become entrepreneurs suddenly without a trigger to be interested in entrepreneurship. According to Hernawati and Yuliniar (2019), entrepreneurial interest or intention is an individual's tendency to take business actions by creating new products and taking risks through opportunities. People need an interest in entrepreneurship to strive for in the future in connection with desires, hopes, ambitions, aspirations, or plans.…”
Section: Entrepreneurial Intentionmentioning
confidence: 99%
“…People cannot become entrepreneurs suddenly without a trigger to be interested in entrepreneurship. According to Hernawati and Yuliniar (2019), entrepreneurial interest or intention is an individual's tendency to take business actions by creating new products and taking risks through opportunities. People need an interest in entrepreneurship to strive for in the future in connection with desires, hopes, ambitions, aspirations, or plans.…”
Section: Entrepreneurial Intentionmentioning
confidence: 99%
“…Entrepreneurship education is defined as an educational process that applies principles and methodologies to the formation of life skills for students through an integrated curriculum developed at schools or universities (Mulyani, 2011). Lo Choi Tung (2011) in Hernawati & Yuliniar (2018) states that entrepreneurship education is the process of transmitting entrepreneurial knowledge and skills to students to help them exploit a business opportunity. Entrepreneurship education fosters entrepreneurial tendencies and intentions.…”
Section: Entrepreneurship Educationmentioning
confidence: 99%
“…Therefore, it is necessary to hold entrepreneurship education in the form of training or mentoring to support these lecture activities. In addition to research on entrepreneurship education, there are previous studies belonging to Amrullah and Anggrismono (2018) and Hernawati and Yuliniar (2019) which examined the mapping of entrepreneurial interests. Amrullah and Anggrismono (2018) mapped entrepreneurial interests based on study program competencies, and the results showed that more than 50% of students' business interests were not in accordance with their field of competence.…”
Section: Introductionmentioning
confidence: 99%
“…Amrullah and Anggrismono (2018) mapped entrepreneurial interests based on study program competencies, and the results showed that more than 50% of students' business interests were not in accordance with their field of competence. Meanwhile, the results of the mapping of Hernawati and Yuliniar (2019) regarding the potential and interest of students in entrepreneurship show that the factors that influence the interest in entrepreneurship and entrepreneurial behavior have a good influence on students' intentions to become entrepreneurs. Based on these findings, Hernawati and Yuliniar (2019) stated that it is necessary to design an entrepreneurship learning program that can motivate students to become entrepreneurs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation